113k views
5 votes
-x2 - 4x + 21
Factorise

User Porg
by
5.6k points

2 Answers

3 votes
The answer is
= -6x +21
-x2 - 4x + 21 Factorise-example-1
User Gabric
by
5.8k points
2 votes

9514 1404 393

Answer:

-(x -3)(x +7)

Explanation:

Apparently, you're supposed to match the given expression with the parts of the identity ...

(x + a)(x + b) = x² +(a +b) +ab

First of all, we notice that the sign of x² in our given expression is negative. So, we factor -1 out of the expression first.

-x² -4x +21 = -(x² +4x -21)

Now, matching the coefficients of x, and the constant to those in our identity, we see ...

a + b = 4 . . . . . coefficients of x

ab = -21 . . . . . . constants

It is relatively easy to find the factors of -21. We are interested in those factor pairs such that the sum is positive:

-21 = -1(21) = -3(7) = -7(3) . . . . at this point the sum -7+3 becomes negative

The factor pair a=-3, b=7 will satisfy ...

a + b = -3 + 7 = 4

ab = (-3)(7) = -21

So, our factorization is ...

-x² -4x +21 = -(x² +4x -21) = -(x -3)(x +7)

User Kiley
by
5.8k points